Strategic Planning in Digital Marketing: Bibliometric and Content Analysis - Irene Kanina Ratih; Muhammad Saad Salahudin; Syarifa Hanoum; Jaroslaw Korpysa (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2023)
Purpose – This study is aimed to map the trend, conceptual structure, and characteristic of strategic planning in digital marketing research. Methodology – This study uses Performance Bibliometrics analysis and Science Mapping Techniques. Performance Bibliometrics is used to analyze basic information and Science Mapping Techniques are used to find differences in future studies. the PRISMA method was used to complete the analysis performed. Findings – the most prolific and influential journals, authors, countries, and research dominated by Spain, the United States, and the United Kingdom. In addition, four themes are found that are often used in this field of study, namely the